Sustainability Performance and Sustainable Development Goals - Nofryanti; Sembel, Roy; Augustine, Yvonne; Arsjah, Regina Jansen (International Journal of Sustainable Development & World Policy, 2021)
The purpose of this study was to examine the effect of sustainability performance on the achievement of sustainable development goals (SDGs). This study examines each of the sustainability performance indicators consisting of economic performance, social performance and environmental performance on the achievement of sustainable development goals. The data used in this study are primary data. This study used a quantitative approach with a questionnaire survey model given to division managers in go public companies in the manufacturing sector in Indonesia. The questionnaires that can be processed are 124 respondents from 42 manufacturing companies listed on the Indonesia Stock Exchange that publish annual reports. Methods of data analysis using structural equation modeling with the help of the Smart PLS application. The results showed that the social and environmental performance that has been achieved by the company was seen as capable of supporting the achievement of the SDGs, but that the economic performance has no impact on the SDGs.